Antibothrus morimotoi Sasaji, an Old World cocoon-forming beetle (Coleoptera: Coccinelloidea: Bothrideridae) newly established in North America - Mcelrath, Thomas C.; Androw, Robert A.; Mchugh, Joseph V. (Zootaxa, 2016)
Antibothrus morimotoi Sasaji, a cocoon-forming beetle (Coccinelloidea: Bothrideridae) native to the Palearctic region, is newly reported from North America. In 2013 and 2015, several series of specimens were collected during an ongoing USDA/APHIS/PPQ exotic bark beetle survey in Franklin County, Ohio, U.S.A. This is the first confirmed record of the species and genus in the New World. The capture of these specimens suggests that the beetle is established in the greater Columbus, Ohio, metropolitan  area.